Implementasi Algoritma Winnowing Pada Aplikasi Ensiklopedia Alam - Syaiful Syaiful (Bulletin of Information System Research, 2022)
Encyclopedia is a summary that contains information on the field of science being discussed. Nature is everything that exists on this earth, be it geology or the living things in it. But in this modern era, there is still no special application that helps to access knowledge and information related to nature. Searching for information about nature through browsing has to go through different web pages, this is not very effective because it takes time and is certainly not efficient. The solution to the problem is with the Natural Encyclopedia search application which uses a string matching algorithm, which is an algorithm that can search for words (patterns) in a text sentence (string) to find a word and display a word found in the text. Winnowing algorithm is used in similarity detection using hashing function. Winnowing is an algorithm used to perform the document fingerprinting process.